Culture and heritage: oral history - McCarthy, Louella; Ashton, Paul, 1959-; Graham, Hamish; Australia. Environment Australia; Australia. Department of the Environment (Canberra : Environment Australia, Department of the Environment, 1997)
Culture and heritage: oral history represents the results of the first major survey of its kind into oral history practice in Australia. Research findings are provided on local history, oral history and oral traditions practised in Australia in relation to heritage work. Changes which have affected heritage practice over the past ten years are identified and a list of key indicators and base-line data are provided.
Bibliography: p. 19-21.
Keywords: Oral history; Oral history -- Government policy -- Australia; Australia -- History -- Methodology